Primary gastric Burkitt lymphoma-induced anaemia: a case report and a literature review - Kapitančukė, Monika; Vaščiūnaitė, Agnija; Augustinienė, Rasa; Sakalinskienė, Jūratė; Kleinotienė, Gražina (Acta medica Lituanica, 2018)
Background. Primary tumours of the gastrointestinal tract are very uncommon in children. They can present with anaemia caused by gastrointestinal acute or chronic bleeding. One of the most common gastrointestinal tumours is Burkitt lymphoma. This lymphoma is a highly aggressive, rapidly growing B-cell neoplasm, making survival without treatment possible only for a few weeks. For this reason it requires immediate hospitalization and treatment. Case report. We report a case of a gastric Burkitt lymphoma in an adolescent girl who presented with anaemia due to gastrointestinal bleeding. She received out-patient care with iron medications orally due to suspected iron-deficiency anaemia but there was no sufficient effect. The patient was referred to Children’s Oncohematology Department with a progression of symptoms (weakness, fatigue, sound in the ears, and nausea) five months after anaemia was diagnosed in the complete blood count. The imaging tests showed a massive solid tumour with bleeding in the stomach. The final diagnosis was a histologically atypical Burkitt lymphoma. Chemotherapy treatment was started according to NHL-BFM 2004 paediatric protocol. Conclusions. Non-Hodgin’s lymphoma is the most common malignancy of the gastrointestinal tract in children and about 75% of these tumours are Burkitt lymphomas. They can present with anaemia in the complete blood count due to bleeding. Reticulocyte test and serum ferritin level test help to differentiate pathophysiological origin of anaemia. Combination chemotherapy according to standardized protocols is the best current standard of care and has a very good clinical response without unfavourable risk factors.